02 General scientific and philosophical approaches to the analysis of training teaching staff of preschool education - Gregory TERESHCHUK; Maria OLIYNYK (Association of Social and Educational Innovation, 2016)
This article analyzes the general scientific and philosophical approaches to the training of teaching staff of preschool education. The essence of the concept of "methodological approach" has been revealed, as did the main approaches to training future educators. Author determined and allocated philosophical, interdisciplinary, systemic, synergistic, functional, personal, activity, axiological, and competency approaches.